In the Wild - Operation Lemur with John Cleese a BBC Production - Kershaw, Justine; Eley, Mike; Cleese, John (IMC Vision, 2002)
Cleese had a lifelong obsession with the lemurs of Madagascar - he first fell in love with a ringtail lemur at the tender age of 12. Last year, he raised money to release five black and white ruffed lemurs born in captivity back into the rainforests of Madagascar. The U.S.-bred "Carolina Five," as these lemurs are affectionately known, are the first lemurs ever to be released into the wild. The hope is that they will survive and eventually mate with the existing population of lemurs to introduce new genes into the population. Then came the difficult bit. John Cleese set out on a three-week trek to go out and find the lemurs. On his journey into the jungle, he comes nose to nose with some of Madagascar's dinosaur-like chameleons, discusses football with a troop of ringtail lemurs, bounds through the forest with dancing sifakas, and shares dinner with the evil-looking aye-aye ... Plagued by a dodgy knee, but cloaked in the full armor of his inimitable wit, Cleese fights his way through the jungle to catch a glimpse of these pioneer balls of fluff. If the ruffed lemur project is a success, the process could be repeated to help save many of the other 32 species of lemur who are now teetering on the brink of extinction. [www.pbs.org]